2020
DOI: 10.2147/rmhp.s223042
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug Utilization Pattern of Antibiotics: The Role of Age, Sex and Municipalities in Determining Variation</p>

Abstract: Purpose: The purpose was to analyze drug prescription and antibiotic use by age and sex in Italy's Campania Region, and to estimate the distribution of prescription rates in children (≤14 years old), adults (between 15 and 65 years old), and older adults (≥65 years old) at a municipality level. Methods: This was a retrospective analysis of pharmacy records in Campania (Southern Italy), in 2016. Difference in antibiotic prescriptions in different age groups was assessed by prevalence rates. Age-adjusted prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
4
24
2
Order By: Relevance
“…Beta [13] lactam was the most common class of antibiotic prescribed in this study, which is in accordance with the study conducted by Orlando V et al . [14] 145 out of 400 prescriptions (36.25%) were found to be containing Fixed Dose Combination (FDC) in present study, the nding which coincides with the results reported by Belhekar MN et al Since FDCs reduce the actual quantity of dosage forms to be taken by the patient, it helps to improve the adherence to treatment by increasing compliance of the patients . 78.46 % drugs were found to be prescribed from the [15] National List of Essential Medicines (NLEM) 2015 and 67.22 % drugs were from WHO List of essential medicine 2019 in this study.…”
Section: B) Gender-wise Distribution Of Study Participantssupporting
confidence: 91%
“…Beta [13] lactam was the most common class of antibiotic prescribed in this study, which is in accordance with the study conducted by Orlando V et al . [14] 145 out of 400 prescriptions (36.25%) were found to be containing Fixed Dose Combination (FDC) in present study, the nding which coincides with the results reported by Belhekar MN et al Since FDCs reduce the actual quantity of dosage forms to be taken by the patient, it helps to improve the adherence to treatment by increasing compliance of the patients . 78.46 % drugs were found to be prescribed from the [15] National List of Essential Medicines (NLEM) 2015 and 67.22 % drugs were from WHO List of essential medicine 2019 in this study.…”
Section: B) Gender-wise Distribution Of Study Participantssupporting
confidence: 91%
“…The Campania Region Database (CaReDB) includes information on patient demographics, the electronic records of outpatient pharmacy dispensing and hospital discharges for ~6 million residents of a well-defined population in Italy (~10% of the population of Italy). CaReDB is complete and includes validated data in previous drug utilization studies [9][10][11][12][13][14][15][16][17]. The characteristics of CaReDB are described in S1 Table. From the beginning of the Covid-19 epidemic, a surveillance system was implemented to collect all cases identified by reverse transcription-polymerase chain reaction (RT-PCR) testing for SARS-CoV-2.…”
Section: Target Population and Data Sourcementioning
confidence: 99%
“…In Italy, many health policies are designed and implemented at Regional level. Among these, there may be indications orienting the prescribing practice, essentially with the aim of cost containment (for example, towards the choice of drugs with comparable efficacy but lower costs) or of risk minimization (for example, towards the choice of drugs associated with a better tolerability profile of with less reporting of medication errors or adverse events) (Russo et al, 2018;Orlando et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such variations may be dependent upon differences in the prescribing habits of general practitioners (GPs) and socioeconomic status of patients (Odubanjo et al, 2004). Furthermore, variations in prescription patterns among different regions and between areas within the same region in Italy have been documented (Russo et al, 2018;Orlando et al, 2020). For instance, the Italian National Observatory on Drug Prescription (OsMed) revealed that, in 2016, the overall prescription for all reimbursed drugs, expressed in defined daily doses (DDDs) per 1,000 inhabitants per day, was 900.7 in northern Italy and 1,048.8 in southern Italy (Rapporto OsMed, 2018).…”
Section: Introductionmentioning
confidence: 99%